The incidence of post‐transplant malignancies in kidney transplant recipients treated with Rituximab. Issue 2 (12th December 2020) - Bachelet, Thomas; Visentin, Jonathan; Davis, Philippine; Taton, Benjamin; Guidicelli, Gwendaline; Kaminski, Hannah; Merville, Pierre; Couzi, Lionel
Abstract: Background: Rituximab has been proposed as induction therapy in kidney transplant recipients (KTRs) with preformed donor‐specific antibodies (DSA) or a positive flow cross‐match. We here evaluated whether adding rituximab was associated with a higher incidence of post‐transplant malignancies (PTM) due to greater immunosuppression. Patients and Methods: Forty‐eight HLA‐sensitized KTRs received induction therapy with anti‐thymocyte globulin (ATG) and rituximab because of preformed DSA or a positive flow cross‐match (RTX group). They were compared with a control group of 154 patients receiving ATG alone. Results: Thirty‐nine of 202 (19.3%) patients developed PTM; the rate was similar in the RTX and no‐RTX groups (14.6% vs. 20.8%, respectively, P = .3). The distributions of the types of cancer were similar between the two groups, with the majority being non‐melanoma skin cancer (NMSC, n = 24). The risk factors for PTM were male gender, age, history of cancer, and azathioprine. Conclusion: Our data do not indicate a higher rate of post‐transplantation de novo malignancies after kidney transplantation in high‐immunological risk patients who received induction therapy based on ATG and rituximab.